Analisis Penerapan Informasi Akuntansi Pertanggungjawaban Pada Perusahaan Deroyal Tour & Travel - Suarta, I Gede; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 34 No 10 (2024)DO - 10.24843/EJA.2024.v34.i10.p09, 2024)
This study aims to determine and analyze how the application of accountability accounting information to the Deroyal Tour & Travel Company. The method used is descriptive qualitative analysis. The results of this study indicate that responsibility accounting has a positive effect on the application of responsibility accounting information at the Deroyal Tour & Travel company. Deroyal Tour & Travel has been equipped with an organizational structure, Deroyal Tour & Travel has made a management budget report, has created an account code, and does not yet have a report of controlled and uncontrolled costs, and has not made an accountability report.